α-Heteroatom-substituted gem-Bisphosphonates: Advances in the Synthesis and Prospects for Biomedical Application - Romanenko, Vadim D. (Current Organic Chemistry, 2019)
Functionalized gem-bisphosphonic acid derivatives being pyrophosphate isosteres are of great synthetic and biological interest since they are currently the most important class of drugs developed for the treatment of diseases associated with the disorder of calcium metabolism, including osteoporosis, Paget’s disease, and hypercalcemia. In this article, we will try to give an in-depth overview of the methods for obtaining α- heteroatom-substituted methylenebisphosphonates and acquaint the reader with the synthetic strategies that are used to develop biologically important compounds of this type.
Keywords: enzyme inhibitors